Ethical Issues Related to Brain Organoid Research - Hyun, Insoo (Brain Res, 2020)
This review provides a snapshot of the current ethical issues related to research with human brain organoids. The issues fall into the following main themes: research oversight; human biomaterials procurement and donor consent; translational delivery; animal research; and organoid consciousness and moral status. Each of these areas poses challenges for researchers, bioethicists, regulators, research institutions, and tissue banks. However, progress can be made if these parties build on past experiences with stem cell research, ethics, and policy, but adapted accordingly to new aspects of brain organoid research.